Monoclonal gammopathy leading to blood hyperviscosity syndrome in a dog – case report - Bitencourt, R. C. [UNESP]; Moroz, L. R.; Oriá, A. P. (FapUNIFESP (SciELO), 2024)
Monoclonal gammopathy (MG) is rare in dogs and multiple myeloma (MM) is its main cause. This study reports the case of a female dog which presented MG associated with a MM and consequent blood hyperviscosity syndrome (HVS). Patient presented systemic hypertension, renal disease, chorioretinitis and secondary glaucoma due to HVS. Serological tests for leishmaniasis and for ehrlichiosis demonstrated negative and score 4 from 5, respectively. Non-regenerative anemia, thrombocytopenia, hyperproteinemia, hypoalbuminemia, hyperglobulinemia, creatinine and blood urea nitrogen (BUN) increases, hypercalcemia, hyperphosphatemia, proteinuria, decreased urinary density, and monoclonal peak of gamma globulins were observed. First myelogram identified 81% of medullary plasmacytosis which suggested MM. Plasmapheresis and chemotherapy with melphalan and prednisolone were performed with positive results. The treatment was effective with complete remission of HVS signs, medullary plasmocytosis reduction (21, 8%) and malignant criteria decrease, as well as neoplastic control.
Gamopatia monoclonal com síndrome da hiperviscosidade sanguínea em cão – relato de caso
Keywords: chemotherapy; gamaglobulinas; gamma globulins; leishmaniose; medullary plasmocytosis; mieloma; myeloma; neoplasia; plasmocitose medular; quimioterapia